Non-normative Bodies, Queer Identities: Marginalizing Queer Girls in YA Dystopian Literature. Issue 1 (1st March 2019) - Green-Barteet, Miranda A.; Coste, Jill
Abstract : In this article we consider the absence of queer female protagonists in dystopian Young Adult (YA) fiction and examine how texts with queer protagonists rely on heteronormative frameworks. Often seen as progressive, dystopian YA fiction features rebellious teen girls resisting the restrictive norms of their societies, but it frequently sidelines queerness in favor of heteronormative romance for its predominantly white, able-bodied protagonists. We analyze The Scorpion Rules (2015) and Love in the Time of Global Warming (2013), both of which feature queer girl protagonists, and conclude that these texts ultimately marginalize that queerness. While they offer readers queer female protagonists, they also equate queerness with non-normative bodies and reaffirm heteronormativity. The rebellion of both protagonists effectively distances them from the queer agency they have developed throughout the narratives.